Quantization of the Proca field in the Rindler wedge and the interaction of uniformly accelerated currents with massive vector bosons from the Unruh thermal bath - Castineiras, Jorge; Correa, Emerson B. S.; Crispino, Luis C. B.; Matsas, George Emanuel Avraam [UNESP] (Amer Physical Soc, 2011)
We canonically quantize the Proca field in the Rindler wedge and compute the total response rate of a uniformly accelerated current interacting with massive vector Rindler particles from the Unruh thermal bath. We explicitly verify that the result obtained is exactly the same as the emission rate of massive vector particles in the Minkowski vacuum as analyzed by inertial observers. Eventually, our results are interpreted in terms of the interaction of static electrons coupled to Z(0) bosons present in Hawking radiation close to the event horizon of a black hole.